Investigating the Prevalence of Undiagnosed Diabetes and Its Associated Factors Among Healthcare Workers: A Cross-sectional Study in South of Iran - Ali Zamani; Kasra Assadian; Seyed Jalil Masoumi; Nadia Mohammadi Dashtaki; Fariba Moradi Ardekani; Elahe Mansouriyekta; Alireza Mirahmadizadeh (Journal of Diabetology)
Context: Undiagnosed diabetes mellitus (DM) is a hidden aspect of the diabetes epidemic. Globally, over 50% of cases are estimated to be undiagnosed. Undiagnosed DM poses serious public health concerns due to increased risks of complications.